Pregnant Mothers Perception About Covid-19 to Compliance with the Use of Mask at Mungkid Magelang Health Center - Salis Atiqoh; Rohmayanti Rohmayanti; Kartika Wijayanti (Universitas Respati Yogyakarta, 2023)
Pregnant women are a susceptible group to covid-19 infection due to pregnant women, in general, are vulnerable to respiratory infection. One of the prevention measures is the use of masks which will help to protect against and limit the spread of Covid-19. This study contributes to identifying the relationship between perception and mask use adherence among pregnant women in Mungkin Public Health, Magelang. A cross-sectional study with 87 pregnant women was selected using the random sampling technique in Mungkin Health Center, Magelang. The questionnaire used was a perception questionnaire about Covid-19 with a validity test of r > 0.3 and a validity test of 0.721. The compliance questionnaire had a validity value of r table 0.3 and a validity test of 0.723, and the data were analyzed using the Spearman statistical test. The majority of respondents were aged 20–35 years, working (65.5%), with gestational age in the second trimester (63.2%), and in secondary education (82.8%). Most of the respondents have a moderate perception regarding mask use during Covid-19 (56.3%), and 23% have a good perception. Regarding adherence to mask use, 62 (71%) respondents have moderate adherence, and 18 (20%) have poor adherence. There is a statistically significant relationship between perception and mask use adherence among pregnant women in Magelang (p = 0.000). Since there is an association between perception and mask use adherence, interventions to promote mask use are needed among pregnant women.